Gestão de resíduos orgânicos gerados no restaurante do IFAM-CMDI e a distribuição de alimentos pela assistência estudantil - IFAM-CMDI - Alencar, Vanessa Galvão (Brasil, 2021)
The generation of organic waste in Brazil, has alarming data, there is a culture of waste in the country, this fact was verified in an educational institution in the provision of daily meals to students who participate in a PNAES. However, not all students who submit to the edict are considered due to insufficient resources. Faced with this was thought how to reduce the waste of food, as well as the disposal of organic waste, reverting them in more benefits. In this way interviews and weighing and in loco observation of the wasted foods and the causes of this done, as well as possible solutions were made. Therefore, the objective of the research, from the standpoint of environmental management and reverse logistics, was to elaborate a data collection about the distribution of food and evaluate the effectiveness of the supply chain management and its characteristics. To point out how logistics works in this food supply process at IFAM - CMDI. Thus, during the month of analysis, the average number of dishes served to the 220 students was approximately 800 grams of food per dish, thus calculating the total wasted in the month, which was 124 kg of waste ingestion and 254 kg of bark of the preparation, it can be said that approximately 472 food dishes could have been provided the most in the month, benefiting more students with the social benefit related to food. If the knowledge of management and reverse logistics is implemented to make food distribution more effective, with fewer losses and to analyze ways of transforming losses into gains, within an educational process, it will be possible to contribute to a better service of the PNAES.